ATR-FTIR Method for Detection of Cassava Impurities in Indonesian Commercial White Pepper (Piper nigrum L.) Based on Principal Component Analysis - Asnawi, Aiyi; Fitriani, Ajeng; Febrina, Ellin; Emawati, Emma (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2021)
White pepper (Piper nigrum L.) is one of the most popular flavourings targeted for adulteration, i.e., cassava, resulting in quality loss and infringement on consumer rights and interests. Because it is easy and quick cleanup, minimal sample preparation, and excellent performance with strongly or thickly absorbed samples, the Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy (ATR-FTIR) spectrum signal is widely used to measure commercial herbal products. Manipulation of the spectrum signal can be used to quantify a sample as well as reduce its dimensionality. As a result, there is a lot of interest in developing methods for detecting cassava in commercial white pepper (Piper nigrum L.). The aim of the research was to get an ATR-FTIR spectroscopic technique combined with chemometrics to detect cassava as an adulterant in commercial white pepper (Piper nigrum L.). The chemical profiles of white pepper (Piper nigrum L.) and cassava were compared using principal component analysis (PCA). Bangka, Sudu, and Pontianak were used to collect white pepper (Piper nigrum L.) and cassava. White pepper (Piper nigrum L.) and cassava were macerated in 96 percent ethanol for 3×24 hours before being concentrated with a rotary evaporator until thick. Each extract’s IR spectral was measured using ATR-FTIR spectroscopy in the 4000-650 cm-1range. In addition, the IR spectral was clustered using PCA in the R program. To obtain the appropriate PCA model, we applied two IR spectral manipulation procedures (normal and derivative IR spectra) of the pure material. The PCA chosen was of the normal IR spectral type, with PC1 and PC2 values of 82.3 percent and 7.5 percent, respectively.. The projection of three commercial samples from the markets revealed that samples A and B were negative for cassava adulterant, while Sample C was suspected to be positive. Finally, the ATR-FTIR spectroscopic method tandem PCA was successful in clustering the presence or absence of cassava content in the commercial of Indonesian White Pepper